EVGE 2011 AWARD - Mouzouropoulos, Theseas (My University, 2026)
The award was received by the Greek Graphic Design & Illustration Awards for the exemplary design and concept in the category Infographic Design. The project with the title “Global Walls Now” presents all the partitions that exists on Earth preventing the movement of people and contributing to their separation because of political, religious or economic conflicts. The purity of the execution and the rendition of this project’s design concept serves to inform in a direct and concise manner on all the existing diving barriers, their categorisation and their current situation as well as on those under construction or scheduled to be constructed
Keywords: Arts and entertainment